Evaluation of ash composition and deposition tendencies of biomasses and torrefied products from woody and shrubby feedstocks: SRC poplar clones and common broom. (1st June 2020) - Rodrigues, A.; Nunes, L.J.R.
Abstract: This work intended to compare ash composition and deposition tendencies biomasses and of torrefied products of SRC poplar clones and common broom. These biomasses were assessed in a previous study as these delivering torrefied products with better fuel quality. Ash analysis for quantification of inorganic major and minor ash elements of biomasses and torrefied products was performed with an inductively coupled plasma- optical emission spectrometer (ICP-OES). The ash melting profiles were experimentally determined. These results allowed the calculation of empirical indexes for evaluation of slagging and fouling tendencies. Independence was established between torrefaction dynamics properties such as mass loss, fixed carbon, volatiles and ash inorganic components for biomasses and torrefied products and with physical–chemical deposition indexes. Results showed that biomasses and torrefied products of common broom and in a lesser extent of AF2 and AF8 poplar clones were prone to a silicate melt induced slagging pattern, whilst the other poplar clones' feedstocks should exhibit an alkali induced slagging profile. Correlation analysis showed different patterns of interconnectedness of ash elements and physical properties for biomasses and torrefied products. For example, initial deformation, hemispheric and flow temperature and alkali indexes were shown with higher relevance for characterization of slag/foul tendencies in biomasses and ash fusibility index, although fundamental for both feedstocks, were more influenced by oxides in torrefied biomasses. In non-torrefied products the major interaction of temperature indexes was observed with alkali indexes. The two databases generated in this work on ash composition and properties of biomasses and torrefied products can contribute to planning of research actions on biomass torrefaction as a tool for upgrading of solid biofuel qualities.